2021
DOI: 10.3389/fpls.2021.748829
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study Identifies Genomic Regions for Important Morpho-Agronomic Traits in Mesoamerican Common Bean

Abstract: The population growth trend in recent decades has resulted in continuing efforts to guarantee food security in which leguminous plants, such as the common bean (Phaseolus vulgaris L.), play a particularly important role as they are relatively cheap and have high nutritional value. To meet this demand for food, the main target for genetic improvement programs is to increase productivity, which is a complex quantitative trait influenced by many component traits. This research aims to identify Quantitative Trait … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 72 publications
1
11
0
Order By: Relevance
“…>10-12-15 H 2 = 0.00-0.74 r = 0.23-0.71 Martin and Wilcox, 1973;Costa et al, 2008;Ramteke et al, 2012;Kang et al, 2017;Teixeira et al, 2017;Beiküfner et al, 2019;Seferova and Bulakh, 2019;Rêbilas et al, 2020;Sobko et al, 2020;Borowska and Prusiñski, 2021;Khadka et al, 2021 Common bean (Phaseolus vulgaris L.) 15 h 2 = 0.68-0.92 r = 0.43-0.69 Bisognin et al, 2019;Nadeem et al, 2020;Delfini et al, 2021;Girgel, 2021 Chickpea (Cicer arietinum L.)…”
Section: R (Hfp/ Ph) Reference Soybean [Glycine Max(l) Merr]mentioning
confidence: 99%
See 2 more Smart Citations
“…>10-12-15 H 2 = 0.00-0.74 r = 0.23-0.71 Martin and Wilcox, 1973;Costa et al, 2008;Ramteke et al, 2012;Kang et al, 2017;Teixeira et al, 2017;Beiküfner et al, 2019;Seferova and Bulakh, 2019;Rêbilas et al, 2020;Sobko et al, 2020;Borowska and Prusiñski, 2021;Khadka et al, 2021 Common bean (Phaseolus vulgaris L.) 15 h 2 = 0.68-0.92 r = 0.43-0.69 Bisognin et al, 2019;Nadeem et al, 2020;Delfini et al, 2021;Girgel, 2021 Chickpea (Cicer arietinum L.)…”
Section: R (Hfp/ Ph) Reference Soybean [Glycine Max(l) Merr]mentioning
confidence: 99%
“…Phvul.006G098300 = BEBT, Benzyl alcohol O-benzoyltransferase. Delfini et al, 2021 Phvul.006G098200 = WD40 or WDR, WD40-repeat gene. Alternative candidate gene.…”
Section: Jaudal Et Al 2018mentioning
confidence: 99%
See 1 more Smart Citation
“…Next generation sequencing (NGS) technologies are important elements of modern plant breeding programs but also pivotal to discovering the genetic diversity of PGRs and selecting genotypes with desired traits [21][22][23]. With regard to runner bean, studies so far have mainly focused on the elucidation of the genetic diversity and evolutionary history of this species, using mostly single sequence repeat (SSR) and inter simple sequence repeat (ISSR) markers [5,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to runner bean, studies so far have mainly focused on the elucidation of the genetic diversity and evolutionary history of this species, using mostly single sequence repeat (SSR) and inter simple sequence repeat (ISSR) markers [5,[24][25][26]. No research has been performed so far linking the observed genetic variability of this species to relevant agronomic traits based on state-of-the-art methods, as has been performed for the closely related common bean through genomewide association studies (GWAS) [21,27,28]. These examples highlight the importance of the combination of NGS data with GWAS to characterize genetic markers associated to (agronomic) traits of relevance, which can be used in selection and breeding programs, as reviewed in [29].…”
Section: Introductionmentioning
confidence: 99%